HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KECEPATAN DENGAN HASIL LOMPAT JAUH PADA SISWA PUTRA KELAS XI SMA NEGERI 1 BENAI - Pietra Jaya; Saripin '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research is based on the results of observations on male students of class XI SMA Negeri 1 Benai. Problems derived from the results of these observations, among others: the average distance of the long jump results of the students still unsatisfactory. Students rate as the prefix is less tight. Adapaun purposes of this study were 1) to determine the ratio of the leg muscles explosive power with a long jump results in male students of class XI SMA Negeri 1 Benai. 2) determine the ratio of the velocity jump results in male students of class XI SMA Negeri 1 Benai. 3) To determine the relationship of the leg muscle explosive strength and speed in the long jump results in male students of class XI SMA Negeri 1 Benai. This type of research is a kind of research is correlational with 3 variables. The population in this study were all male students of class XI SMA Negeri 1 Benai which counted 40 people. This sampling technique is the total sampling, thus reducing the number of samples in this study were 40 persons. Data-analysis showed that all of the data normally distributed. From the result of the calculation is known that there is a significant correlation between the variables x1, x2 and y variables. The calculation of the variable X1 and Y obtained value r calculated at 0.629. From the table, the value of R value obtained rtabel on df = 38 with significance level (α) 00:05 = 0312. This means that the value of r census 0411> rtabel (0312) concluded, there is a significant relationship between the leg muscles explosive power of the jump from SMA Negeri 1 Benai As a matter of X2 and Y obtained calculated the value of r obtained at 0.332. From the table, the value of R value obtained rtabel on df = 38 with significance level (α) 00:05 = 0312. This means that the value of r count 0.332> r table (0312). a conclusion, there is a link speed with the ability to jump results in SMA Negeri 1 Benai. By way of X1, X2 and Y are obtained by counting results obtained correlation value calculated 0481 r. From the table, the value of R value obtained rtabel on df = 37 with significance level (α) 00:05 = 0316. This means that the value of r census 0481> rtabel (0316). Kesimpulanya a significant relationship between leg muscle explosive power and speed of the results of the long jump at SMA Negeri 1 BenaiKeywords: leg muscle explosive power, speed, long jump2